2011
DOI: 10.1371/journal.pone.0027306
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Antagonist GDC-0449 (Vismodegib) Inhibits Pancreatic Cancer Stem Cell Characteristics: Molecular Mechanisms

Abstract: BackgroundRecent evidence from in vitro and in vivo studies has demonstrated that aberrant reactivation of the Sonic Hedgehog (SHH) signaling pathway regulates genes that promote cellular proliferation in various human cancer stem cells (CSCs). Therefore, the chemotherapeutic agents that inhibit activation of Gli transcription factors have emerged as promising novel therapeutic drugs for pancreatic cancer. GDC-0449 (Vismodegib), orally administrable molecule belonging to the 2-arylpyridine class, inhibits SHH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 49 publications
12
124
1
2
Order By: Relevance
“…Our results suggest that anti-DLL4 can be combined effectively with gemcitabine to block tumor growth through multiple mechanisms. In addition to targeting Notch signaling, we and other investigators have recently shown the feasibility of blocking Wnt, hedgehog, or Nodal/activin to reduce pancreatic CSC frequency (50)(51)(52). New therapeutic approaches targeting pathways important for CSCs may improve treatment and, ultimately, overall survival in this very challenging disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that anti-DLL4 can be combined effectively with gemcitabine to block tumor growth through multiple mechanisms. In addition to targeting Notch signaling, we and other investigators have recently shown the feasibility of blocking Wnt, hedgehog, or Nodal/activin to reduce pancreatic CSC frequency (50)(51)(52). New therapeutic approaches targeting pathways important for CSCs may improve treatment and, ultimately, overall survival in this very challenging disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that the Hh signaling pathway is recruited to stimulate CSC growth. It is one of the key pathways that regulates stem cells in the adult body (38,39). Several studies have also shown that the Hh signaling pathway plays an important role in maintaining the biological characteristics of pancreatic cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological or genetic inhibition of JNK leads to loss of stem cell properties in the pancreatic CSCs both in vitro and tumor. Furthermore, loss of Kras in kras mutant pancreatic CSCs led to the loss of stem cell characteristics by downregulation of the JNK pathway [79] . Pancreatic cancers contain 1%-3% of CD133 positive cancer cells, some of which show high expression of CXCR4, a proinvasive marker [14] .…”
Section: Role Of Pancreatic Cscs In Prevention and Treatmentmentioning
confidence: 99%